Validação de SNPs associados com área de olho de lombo em bovinos Canchim - Lima, Andressa Oliveira de (Universidade Federal de São Carlos, 2014)
The Beef cattle production is a very important economic activity for Brazil, which is a global producer and exporter of bovine-derived products and currently contains the world s largest beef cattle herd. However, the majority Brazilian cattle are adapted to a tropical climate and have low meat and carcass quality. The crossbreeding between Charolais and Zebu animals resulted in development of Canchim breed. This breed shows better resistance to high temperatures and parasites, as well as better meat and carcass quality. New genotyping and computational technologies can enable the use of single nucleotide polymorphism (SNP) in breeding programs. The high demand for meat quality and the aggressive competition among other beef exporting countries justifies studies focused on improving carcass traits, such as ribeye area (REA), which can provide more efficiency production of meat cuts for consumption. The objective in this study was to validate SNPs selected in a previous genomewide association study (GWAS) for REA performed by Random Forest methodology in 400 animals genotyped with the BovineHD BeadChip ( Illumina®) which yielded a set of 197 SNPs. First, we analyzed the linkage disequilibrium (LD), and then we annotated the associated regions. After verifying this set of SNPs, we selected four SNPs located on BTA4, BTA10, BTA22 and BTA27 for validation purposes. These SNPs were genotyped by RFLPPCR in approximately 712 bovine. We analyzed the genetic effect of these SNPs the using GLM procedure in SAS (P ≤ 0,05), which identified SNPs in BTA4 and BTA27 as contributing some genetic effect on REA. Furthermore, we found significant additive effect (P≤ 0,05) for the SNP on BTA 27, and a significant dominance effect for the SNP in BTA 4 using the ASReml software. The GWAS for REA identified one region between 34989224pb and 36989224pb using haplotype association analysis with the PLINK software that indicated two regions (P≤ 0,05) in the SFRP1 and ANK1 genes associated with REA.
Keywords: Bovino - genética; Área de olho de lombo; SNPs; Haplótipos; Canchim (Bovino); Ribeye area; Haplotype; CIENCIAS BIOLOGICAS::GENETICA